Contributing factors on customer retention for sustainability of Malaysian commercial banks / Chim Weng Kong and Maria Abdul Rahman - Chim, Weng Kong; Abdul Rahman, Maria (Universiti Teknologi MARA, Kedah, 2021)
Bank management has a great responsibility to generate enough revenue to keep the bank running. Due to stiff competition among the banks in Malaysia, it is significantly importance of retaining its customers in order to be sustainable and competitive. Customer retention can reward banks with their continuous support with repeat purchases which directly contribute to a stream of revenues. Additionally, customers can contribute positive word-ofmouth and referral that serve as a "walking advertisement" by providing recommendations that are more workable than the bank spending on advertisement fees. As shown in the banks' yearly financial record for the past decade, their profit was inconsistent. The challenges facing the banking industry seem unimaginable due to th Business e stiff competition among the banks to attract customers. The banking industry is expected to face dramatic in customer retention. With the execution of relationship marketing and pricing, the chances for the bank's success and growth will be secured. Marketing is based on a relationship in understanding customers' needs by initiating close bonding between bank employees and customers. Therefore, this paper intends to discuss factors that may contribute to customer retention in the banking industry by apply ing relationship marketing and pricing factors that lead to customers' repeat purchases.